Immunohistochemical Expression of Vegf in Renal Cell Carcinoma and Its Correlation with Clinic morphological Features - V, Govardhani; Amitkumar, Kalaivani (Journal of Neonatal Surgery, 2025)
INTRODUCTION:Renal Cell Carcinoma (RCC) is the most common renal malignancy in adults, accounting for approximately 90% of kidney cancers. Prognostic and predictive biomarkers play a critical role in understanding RCC progression and guiding targeted therapy. Angiogenesis is a critical step in the growth, invasive progression and metastatic spread of solid tumors. Vascular endothelial growth factor (VEGF) is key regulator of angiogenesis, process of building new blood vessels, which is essential for tumor development and metastasis. Role of VEGF in RCC is not well established. AIM:The aim of our study was to analyse VEGF expression in different histological variants of RCC and its relationship with histological type, tumor grade, pathological stage, necrosis, lymphovascular invasion, other clinicopathological parameters. MATERILAS AND METHODS:A retrospective study was performed using paraffin blocks of Renal cell carcinoma reported between 2018 to 2024. For light microscopy screening, sections were initially stained with haematoxylin and eosin stains. In further sections, a primary antibody against VEGF was applied. The level of VEGF expression in renal cell carcinoma was evaluated using a scoring system. RESULTS:Forty cases with renal cell carcinoma were included. In our study, immunohistochemical positivity showed no significant association with histological type, grade, pathological staging, or lymphovascular invasion (p > 0.05 for all). However, a statistically significant correlation was observed with tumor necrosis (p = 0.015), indicating a potential link between marker expression and necrotic changes in renal cell carcinoma. CONCLUSION:In this study of renal cell carcinoma, VEGF expression did not significantly vary by histological type, grade, pathological stage, or lymphovascular invasion. However, a significant inverse association was observed between VEGF expression and tumor necrosis (p = 0.015), indicating that reduced VEGF expression is linked to increased tumor necrosis. These findings suggest that VEGF plays a critical role in maintaining vascular integrity within the tumor microenvironment and may have prognostic significance in RCC